On the strong difference in reactivity of acyclic and cyclic diazodiketones with thioketones: experimental results and quantum-chemical interpretation - Mereshchenko, Andrey S.; Ivanov, Alexey V.; Baranovskii, Viktor I.; Mloston, Grzegorz; Rodina, Ludmila L.; Nikolaev, Valerij A. (Beilstein Journal of Organic Chemistry, 2015)
The 1,3-dipolar cycloaddition of acyclic 2-diazo-1,3-dicarbonyl compounds (DDC) and thioketones preferably occurs with Z,E-conformers and leads to the formation of transient thiocarbonyl ylides in two stages. The thermodynamically favorable further transformation of C=S ylides bearing at least one acyl group is identified as the 1,5-electrocyclization into 1,3-oxathioles. However, in the case of diazomalonates, the dominating process is 1,3-cyclization into thiiranes followed by their spontaneous desulfurization yielding the corresponding alkenes. Finally, carbocyclic diazodiketones are much less reactive under similar conditions due to the locked cyclic structure and are unfavorable for the 1,3-dipolar cycloaddition due to the Z,Z-conformation of the diazo molecule. This structure results in high, positive values of the Gibbs free energy change for the first stage of the cycloaddition process.
Keywords: diazocarbonyl compounds; 1,3-dipolar cycloaddition; 1,3-oxathioles; thiiranes; thiocarbonyl ylides; thioketones